Применение моделей прогнозирования при многомерном контроле процессов загрязнения - Любимова, Н. А. (НТУ "ХПИ", 2014)
Представлены результаты сравнительного анализа дисперсии ошибок прогнозирования (экстраполяции второго порядка) для двух вариантов обработки первичной информации при контроле многомерных (многокомпонентных) процессов промышленного загрязнения окружающей среды. Особенность исследуемой модели прогнозирования – коррекция условного математического ожидания случайного вектора входных сигналов на величину параметра нестационарности, учитывающего асимметрию закона распределения контролируемого процесса. Предложенная модель контроля может быть использована в экологическом мониторинге энергоемких предприятий.

The results of comparative analysis of variance of prediction errors (second-order extrapolation) for two variants of processing of information under the control of multidimensional (multi-components) processes of industrial pollution. The peculiarity of the studied model prediction - correction of the conditional expectation of the random vector of input signals on the value of unsteadiness parameter that takes into account the asymmetry of the distribution law of the controlled process. A model of two-stage computational procedures predict. We can distinguish two ways to use computational procedures in a multivariate forecasting processes in multicomponent emission pollution. The comparative analysis of the options calculated conversion conversion procedures primary information in the test results shows that: Using extrapolation (predictive filters) should take into account the sequence of conversion steps; more effective in the control of random processes forecasting short-term procedures. The proposed control model can be used in environmental monitoring.intensive enterprises.
Application forecasting model of multivariate process control pollution
Keywords: отходы производства; контроль выбросов; прогнозирование; экология; загрязнение; prediction; multi-component; pollution; ecology